Differences in outcome of percutaneous coronary intervention between Indigenous and non-Indigenous people in Victoria, Australia: a multicentre, prospective, observational, cohort study - Dawson, L.P.; Burchill, L.; O'Brien, J.; Dinh, D.; Duffy, S.J.; Stub, D.; Brennan, A.; Clark, D.; Oqueli, E.; Hiew, C.; Freeman, M.; Reid, Christopher; et al. (ELSEVIER SCI LTD, 2021)
Background: Data on the patient characteristics and health outcomes of Indigenous Australians having revascularisation for treatment of coronary artery disease are scarce. The aim of this study was to assess differences in patient characteristics, presentations, and outcomes among Indigenous and non-Indigenous Australians having percutaneous coronary intervention (PCI) in urban and larger regional centres in Victoria, Australia. Methods: In this multicentre, prospective, observational cohort study, data were prospectively collected from six government-funded tertiary hospitals in the state of Victoria, Australia. The Melbourne Interventional Group PCI registry was used to identify patients having PCI at Victorian metropolitan and large regional hospitals between Jan 1, 2005, and Dec 31, 2018. The primary outcome was long-term mortality. Secondary outcomes were 30 day mortality and 30 day major adverse cardiovascular events (MACE), defined as a composite endpoint of death, myocardial infarction, and target-vessel revascularisation. Regression analyses, adjusted for clinically relevant covariates and geographical and socioeconomic indices, were used to establish the influence of Indigenous status on these study outcomes. Findings: 41 146 patient procedures were entered into the registry, of whom 179 (0·4%) were recorded as identifying as Indigenous Australian, 39 855 (96·9%) were not Indigenous Australian, and 1112 (2·7%) had incomplete data regarding ethnicity and were excluded. Compared with their non-Indigenous counterparts, Indigenous patients were younger, more often women, and more likely to have comorbidities. Indigenous Australians were also more likely to live in a regional community and areas of socioeconomic disadvantage. Procedural success and complication rates were similar for Indigenous and non-Indigenous patients having PCI. At 30 day follow-up, Indigenous Australians were more likely to be taking optimal medical therapy, although overall follow-up rates were lower and prevalence of persistent smoking was higher. Multivariable analysis showed that Indigenous status was independently associated with increased risk of long-term mortality (hazard ratio 2·49, 95% CI 1·79–3·48; p<0·0001), 30 day mortality (odds ratio 2·78, 95% CI 1·09–7·12; p=0·033), and 30-day MACE (odds ratio 1·87, 95% CI 1·03–3·39; p=0·039). Interpretation: Indigenous Australians having PCI in urban and larger regional centres are at increased risk of mortality and adverse cardiac events. Clinically effective and culturally safe care pathways are urgently needed to improve health outcomes among Indigenous Australians who are having PCI. Funding: National Health and Medical Research Council, National Heart Foundation.